Epigenetic modifiers during in vitro maturation as a strategy to increase oocyte competence in bovine - Saraiva, Naiara Z.; Oliveira, Clara S.; Almeida, Nathalia N.C.; Figueiró, Marivaldo R.; Quintão, Carolina C.R.; Garcia, Joaquim M. [UNESP] (Elsevier, 2022)
Oocyte in vitro maturation (IVM) is a key procedure for the in vitro production (IVP) of bovine embryos; however, the efficiency of this step is limited by the intrinsic developmental competence of oocytes. This study aimed to investigate possible epigenetic changes resulting from using of histone deacetylase (HDAC) inhibitors in the maturation of bovine oocytes and subsequent embryo development. Initially, we investigated the meiotic progression of bovine oocytes matured in vitro in the presence of trichostatin A (TSA). We then evaluated histone H3k9 acetylation levels in oocytes exposed to different TSA concentrations, and the relative expression of genes linked to oocyte competence. Finally, we studied pre-implantation embryonic development by analyzing the cleavage, blastocysts, and hatching rates. Acetylation levels of H3k9 increased (p < 0.05) when oocytes were exposed to 50 nM or 100 nM TSA during IVM, but there were no significant changes in the relative expression of the evaluated genes p34cdc2, cyclin B1, MAPK, GDF9, G6PDH, and HSP70. We found that 5 nM TSA promoted the attenuation of meiotic progression and positively affected pre-implantation embryo development in bovine species, allowing a 10% increase in the blastocyst rate. We concluded that TSA treatment during IVM was efficient in promoting changes in H3k9 acetylation levels from 50 nM and promoted attenuated meiotic progression in bovine oocytes at all concentrations evaluated, with a positive impact on pre-implantation development when used at low concentrations.
Keywords: Chromatin; Epigenetics; Histone acetylation; Trichostatin A